Diffuse hepatic uptake on bone scan in a terminally ill osteosarcoma patient - Muntaha Fatima Rana; Aamna Hassan (Journal of the Pakistan Medical Association, 2022)
Tc-99m methylene diphosphonate (MDP) bone scan is an effective tool for the evaluation of benign and malignant skeletal disorders. Hepatic uptake on bone scan is an unexpected finding and whenever present, the cause must be determined as the distinction between technical and pathological causes is important to direct further patient management. Identification of these abnormalities will decrease errors and provide cardinal clinical information. We present the image of a patient with Osteosarcoma of the left femur; who underwent bone scan for metastatic workup which showed diffuse hepatic uptake. Keywords: Hepatic uptake, Osteosarcoma, Hepatic artifact.